2018
DOI: 10.1111/hiv.12607
|View full text |Cite
|
Sign up to set email alerts
|

Prospective plasma efavirenz concentration assessment in Chinese HIV‐infected adults enrolled in a large multicentre study

Abstract: Efavirenz concentrations increased steadily over 48 weeks, and a substantial proportion of participants had efavirenz C above the upper limit of the proposed therapeutic window, especially those with low body weight (< 60 kg). Based upon these findings, a dosage reduction of efavirenz to 400 mg daily may warrant consideration in this population, especially for those with lower body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 50 publications
2
17
1
Order By: Relevance
“…As EFV use increased after inclusion in the NFATP, a growing number of patients reported moderate to severe neuropsychiatric symptoms with the standard 600 mg daily dose of EFV, including dizziness, insomnia, nightmares, and depression, as has been reported internationally. The multi-national ENCORE1 studies published in 2014 and 2015 first suggested the non-inferiority of EFV 400 mg to EFV 600 mg daily [9,10], and in a prospective study by the CACT, plasma EFV levels measured in 455 treatment-naïve HIV patients initiated on an EFV-containing regimen showed that 34.2% and 43.8% of participants had plasma EFV concentrations above the upper limit of the proposed therapeutic window at 24 and 48 weeks, respectively, especially in those with low body weight (< 60 kg) [11]. Based on these collective findings, the 2018 Chinese National Guidelines for the Diagnosis and Treatment of HIV/AIDS suggested a dose adjustment for individuals with low body weight [12], and a prospective open-label randomized CACT trial of EFV 400 mg versus 600 mg aimed at collecting real-world evidence among Chinese patients with HIV has just completed enrollment.…”
Section: Optimizing Haart For Chinese Patients With Hivmentioning
confidence: 99%
“…As EFV use increased after inclusion in the NFATP, a growing number of patients reported moderate to severe neuropsychiatric symptoms with the standard 600 mg daily dose of EFV, including dizziness, insomnia, nightmares, and depression, as has been reported internationally. The multi-national ENCORE1 studies published in 2014 and 2015 first suggested the non-inferiority of EFV 400 mg to EFV 600 mg daily [9,10], and in a prospective study by the CACT, plasma EFV levels measured in 455 treatment-naïve HIV patients initiated on an EFV-containing regimen showed that 34.2% and 43.8% of participants had plasma EFV concentrations above the upper limit of the proposed therapeutic window at 24 and 48 weeks, respectively, especially in those with low body weight (< 60 kg) [11]. Based on these collective findings, the 2018 Chinese National Guidelines for the Diagnosis and Treatment of HIV/AIDS suggested a dose adjustment for individuals with low body weight [12], and a prospective open-label randomized CACT trial of EFV 400 mg versus 600 mg aimed at collecting real-world evidence among Chinese patients with HIV has just completed enrollment.…”
Section: Optimizing Haart For Chinese Patients With Hivmentioning
confidence: 99%
“…The studies were carried out by the China AIDS Clinical Trial Network in 11 different municipalities/ provinces in China, including Beijing, Fujian, Guangdong, Guangxi, Henan, Hunan, Liaoning, Shanghai, Shanxi, Sichuan, and Yunnan provinces. The inclusion and exclusion criteria and study-related procedures of these clinical trials have been previously described in detail [18][19][20].…”
Section: Subjectsmentioning
confidence: 99%
“…Previous literatures also showed that weight > 60 kg was associated with lower EFV concentrations in HIV-infected patients [8,14] . In our study, weight of patients at baseline ranged from 47 to 67 kg.…”
Section: Discussionmentioning
confidence: 74%
“…Patients with EFV concentration > 4 mg/L experienced three times more frequent of CNS adverse events [7] . Moreover, our previous multicenter study showed that median plasma EFV concentration increasing gradually over 48 weeks and 43.8% patients had EFV concentration > 4 mg/L in China [8] . This meaned that HIV-infected Chinese adults were more likely to suffer from neuropsychiatric symptoms.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation